2022
DOI: 10.3389/fmed.2022.926754
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Cavity Parameters Evaluated by Hysteroscopy can Predict the Live Birth Rate For Intrauterine Adhesion Patients

Abstract: We aim to establish an objective and accurate prediction model by evaluating the uterine cavity and correlate these key factors with the live birth rate after hysteroscopic adhesiolysis (HA). A total of 457 intrauterine adhesions (IUA) patients were retrospectively enrolled in this study. The participants underwent HA and second-look hysteroscopy at the Third Xiangya Hospital of Central South University. Pregnancy outcomes, including spontaneous live births and no live births (miscarriages and infertility), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…We previously found that an AFS score <4 was a favorable factor for live birth ( 10 ). However, this study did not find any correlation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that an AFS score <4 was a favorable factor for live birth ( 10 ). However, this study did not find any correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Assisted reproductive technology (ART) might be a better choice for patients with recurrent IUA ( 9 ). Visible bilateral fallopian tube ostia or American Fertility Society (AFS) scores of <4 in the hysteroscopic reexamination might predict better live birth ( 10 ). Thin endometrium and the upper and middle segments of endometrial absence have been found to be risk factors for live birth ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we used machine learning algorithms such as decision trees and XGboost to predict the pregnancy outcomes of patients based on clinical data ( Li et al, 2022 ; Zhu et al, 2022 ; Li et al, 2023a ). Zhao et al (2022) also developed a logistic prediction model using clinical parameters such as age, preoperative AFS score, preoperative uterine cavity length, and visibility of bilateral fallopian tube ostia during hysteroscopy review. These methods achieved excellent predictive performance, with AUCs of 0.8–0.9.…”
Section: Discussionmentioning
confidence: 99%
“…Hysteroscopy can comprehensively analyze postoperative uterine cavity morphology and endometrial receptivity ( Smit et al, 2016 ; Craciunas et al, 2019 ), thus becoming the first-line assessment method in clinical practice. Moreover, some studies have shown that postoperative hysteroscopic assessment is more powerful in predicting the fertility outcomes of patients ( Xu et al, 2018 ; Zhao et al, 2022 ). However, without objective indicators, it has difficulties effectively integrating it with ART management for postoperative patients.…”
Section: Introductionmentioning
confidence: 99%
“…Intrauterine adhesion (IUA) is the secondary endometrial injury disease [ 1 ] that leads to amenorrhea, infertility, and poor pregnancy outcomes in assisted reproductive technology (ART) in women of childbearing age. The main etiology of IUA is pregnancy-related curettage, such as post-abortion, miscarriage, and postpartum curettage [ 2 , 3 , 4 ]. These procedures may result in the endometrial basal layer being too impaired to completely repair or restore the endometrium.…”
Section: Introductionmentioning
confidence: 99%